IMPLIKASI PEMBERLAKUAN TARIF 0% ATAS PKB DAN BBNKB KENDARAAN BERMOTOR LISTRIK BERBASIS BATERAI TERHADAP PENERIMAAN PKB DAN BBNKB PROVINSI JAWA TIMUR - Yohanes Roy Bandur; Bayu Sarjono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the impact of the 0% rate policy on Motor Vehicle Tax (MVT) and Motor Vehicle Title Transfer Fee (MVTTF) for Battery Electric Vehicles (BEVs) in relation to regional tax revenues in East Java Province. The fiscal incentive is expected to accelerate the adoption of environmentally friendly vehicles as part of the national strategy to reduce carbon emissions and achieve the net zero emission target. Methods: The research applies a descriptive qualitative approach with data collection techniques consisting of literature review, documentation, and interviews with relevant stakeholders, particularly the Regional Revenue Agency. Results: The results indicate that although the number of BEVs has increased steadily each year, their contribution to regional revenues from MVT and MVTTF over the last four years remains relatively small. However, the rapid growth of BEVs has the potential to create more significant fiscal impacts in the future, especially from four-wheeled electric vehicles that possess higher market value compared to two-wheelers. These findings underline the necessity of policy evaluation and the development of adequate fiscal compensation strategies to ensure that incentives for electric vehicles can continue without undermining regional fiscal sustainability. Accordingly, the study recommends that local governments formulate policies capable of balancing the promotion of eco-friendly vehicle adoption with stable tax revenues. Keywords: Battery Electric Vehicles (BEVs), Motor Vehicle Tax (MVT), Motor Vehicle Title Transfer Fee (MVTTF), Regional Tax, 0% Rate